Necip Fazıl’ın ‘Ruh’unda Hakikatin Göstergeleri: Göstergebilim Açısından Bir Şiir Değerlendirmesi - Bulut, Funda (Erdem, 2020)
In semiotics everything is based on the problem of signification; the real meaning of the poetry can be reached when the points which make contrast and contradiction are revealed. The pre-condition of analysing poem as a semiotic, separating the text into units in order to resolve the meaning bond between units and finding the acquired meaning of the indicator in itself. By reading and analyzing several times, the text can be assessed from the surface to the depth. During many ages, while philosophers and scientists were thinking over words and indicators, they emphasized the basic process of the indicators in finding the genuine reality. Plato expresses that indicators will be missing in finding the genuine reality and these indicators can trip up us as results of perception; Pierce expresses that without indicators there will be no thinking and perception and only genuine reality can be reached via indicators. Necip Fazıl believes as Plato that genuine reality is God and also believes that it is necessary trying to reach the meaning and the reality behind material indicators. The poet continues this manner also in the poem named “Spirit” and it can be said that the poet constructed all the referential semiotical meanings of the poem over an argument sourced from the reality of existence and the dream of vanishing. The semantic richness and depth of Necip Fazıl Kısakürek’s poetry stems from his handling of a long, arduous journey into the inner world of man. This journey, which makes the reader think about being, is a product of the effort to make sense of life. In making sense of existence, the poet tries to explain existence with its opposite absence, as he does not see death as separate from his thoughts and poems. In other words, it can be said that, death for Necip Fazıl is the most important fact of existence and is an important step in the search for genuine reality, especially in the realization of mankind. The current study is a semiotic analysing trial of Necip Fazıl Kısakürek’s poem designated “Spirit”. In this poem, which has a psychological, metaphysical depth and features a multi-layered structure, it is aimed to reveal the truth hidden within the feelings and thoughts that are difficult to separate from each other at first glance. In this study, firstly, formal review of the poem was performed in order to see the surface structure of the poem, and in the second stage, in order to reveal the deep structure of the poem, the display strings indicators were analysed, therefore meaning interactions of the indicators were detected. In conclusion, the contrasts and contradictions that are enriching the meaning world of the poem were determined and poem was analysed. In poetry, the arrival of the soul to the world (known), the unawereness of the mortal people in the city from the presence of another world (eternity, unknown), the soul’s attempt to make itself aware, and the unconsciousness of the people in the city are the main elements that constitute the contrast in poetry.

Her şeyin anlamlama sorununa dayandığı göstergebilimde şiirin asıl anlamına karşıtlık ve çelişiklik yaratan noktalar ortaya çıkarıldığında ulaşılabilir. Şiiri, göstergebilimsel olarak çözümleyebilmenin ön- koşulu metni birimlere ayırarak birimler arasındaki anlam bağını çözmek ve göstergenin kendi içinde kazandığı anlamı bulmaktır. Çağlar boyunca hem filozoflar hem bilim adamları, sözcükler ve göstergeler üzerinde düşünürken göstergelerin hakiki gerçekliği bulmadaki temel işlevi üzerinde durmuştur. Eflatun, hakiki gerçekliği bulmada göstergelerin eksik kalacağını, bu göstergelerin algıların bir ürünü olduğu için bizi yanıltacağını söylerken Pierce, göstergeler olmadan düşünme ve algı olamayacağını söylemekte, hakiki gerçeğe göstergeler üzerinden gidilebileceğini ifade etmektedir. Necip Fazıl da hakiki gerçekliğin Eflatun’daki gibi Tanrı olduğunu, maddî göstergelerin arkasındaki manaya ve hakikate ulaşmaya çalışmanın gerekli olduğunu düşünür. Bu tavrı, “Ruh” şiirinde de sürdüren şairin şiirin bütün göndergesel anlamlarını varoluş gerçeği ile yok oluş hayalinden kaynaklanan bir çatışma üzerine kurduğu söylenebilir. Necip Fazıl Kısakürek şiirinin anlamsal zenginliği ve derinliği, insanın iç dünyasına yapılan uzun, zorlu bir yolculuğu ele almasından kaynaklanmaktadır. Okurun varlık üzerine düşünmesini sağlayan bu yolculuk, yaşamı anlamlandırma çabasının bir ürünüdür. Varoluşu anlamlandırma sırasında şair; ölümü düşüncelerinden ve şiirlerinden ayrı görmediği için varlığı onun zıddı olan yoklukla açıklamaya çalışır. Bir başka deyişle Necip Fazıl için ölüm, varoluşun en önemli gerçeğidir ve hakiki gerçekliği arayışta özellikle insanoğlunun idrakinde önemli bir basamaktır, denilebilir. Bu çalışma, Necip Fazıl Kısakürek’in “Ruh” adlı şiirinin göstergebilimsel açıdan çözümleme denemesidir. Psikolojik, metafizik bir derinliğe sahip olan ve çok katmanlı bir yapı özelliği gösteren bu şiirde ilk bakışta birbirinden ayrılması zor olan duygu ve düşüncenin içine gizlenmiş hakikati ortaya çıkarmak hedeflenmektedir. Çalışmada ilk olarak şiirin yüzey yapısını görebilmek için şiirin biçimsel incelemesi yapılmıştır. İkinci aşamada ise şiirin derin yapısını ortaya çıkarmak amacıyla gösterge dizgeleri çözümlenerek göstergelerin birbiriyle kurdukları anlam ilişkileri tespit edilmiştir. Böylelikle şiirin anlam dünyasını zenginleştiren “karşıtlıklar ve çelişkiler” belirlenerek şiir çözümlenmeye çalışılmıştır. Şiirde ruhun dünyaya (bilinenene) gelişi, şehirdeki fani insanların başka bir dünyadan habersiz olması (sonsuzluk, bilinmeyen), ruhun kendini fark ettirmeye çalışması ve şehirdeki insanların bilinçsizliği şiirdeki karşıtlığı oluşturan başlıca ögelerdir. Bütün sözcüklerin ve göstergelerin okuyucuyu varoluş gerçeği üzerine düşündürdüğü şiirde temel ileti, “varoluşun yok oluş üzerinden idraki ve maddi hayatın geçiciliği” olduğu söylenebilir.
Keywords: Displaying; semiotics; poetry; semiotic analysis; Necip Fazıl Kısakürek; Spirit; Gösterge; göstergebilim; şiir; Necip Fazıl Kısakürek; ruh